Design at hackathons: new opportunities for design research. (22nd February 2021) - Flus, Meagan; Hurst, Ada
Abstract: Hackathons are short-term events at which participants work in small groups to ideate, develop and present a solution to a problem. Despite their popularity, and significant relevance to design research, they have only recently come into research focus. This study presents a review of the existing literature on the characteristics of designing at hackathons. Hackathon participants are found to follow typical divergence–convergence patterns in their design process throughout the hackathon. Unique features include the initial effort to form teams and the significant emphasis on preparing and delivering a solution demo at the final pitch. Therefore, hackathons present themselves as a unique setting in which design is conducted and learned, and by extension, can be studied. Overall, the review provides a foundation to inform future research on design at hackathons. Methodological limitations of current studies on hackathons are discussed and the feasibility of more systematic studies of design in these types of settings is assessed. Further, we explore how the unique nature of the hackathon format and the diverse profiles of hackathon participants with regards to subject matter knowledge, design expertise and prior hackathon experience may affect design cognition and behaviour at each stage of the design process in distinctive ways.